A Feasibility Study of Mini-Hydroelectric Power Plant for Seasonal Base Load - Ozigis, I. I.; Oodo, S. O.; Muhammad, I. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This paper presents a feasibility study of a mini-hydroelectric power plant for seasonal base load at the main campus of University of Abuja, along Airport Expressway, Abuja, Nigeria. The study was premised on the need to mitigate the insufficient electricity supply being experienced by  the University. The use of backup diesel and petrol generating sets was noted to increased the overall operating costs of the University due to the need to purchase fuel, in addition to the associated maintenance cost. The presence of River Wuye within the University brought to fore the need to explore the establishment of a hydropower plant as an alternative means of mininmizing the energy shortage. The methodology adopted included determination of the University electricity demand using clamp-on meter, determination of the river run-off via data obtained from Nigerian Meteorological Agency (NIMET), flow rate with the use of float and river geometry, while the head was obtained by Global Positioning System (GPS). Furthermore, the hydroelectric power potential, site layout for equipment installation and project cost were determined. The results indicated that the monthly lowest energy consumption (base load) at the University during the period of study was at 667 kW, while the highest (peak) load was 883 kW. River Wuye assessment favoured conventional hydro power plant instead of  hydro power plant technologies with out dam such as paddle wheel system as Giri river flow was low and seasonal. River Giri  has run-off of 1,330 mm with the proposed dam estimated to have height and length of 10 m  and 120 m, respectively. River Wuye has a flow rate of 14.5 m3/s, maximum head of 10 m and hydropower potential of about 855 kW. The cost of the proposed hydro power plant ranged from 80.3-615.6 million Naira (N) (equivalent to N93,960/kW- N720,000/kW or $261/kW-$2000/kW).The range arose due to variation on cost of refurbished or new turbine-generator system and civil works. The electricity generation unit cost from the hydropower plant is expected to be N24.74-50.14/kWh. This feasibility work is significant as it will aid commencement of detailed project report (DPR) that will highlight detailed study of hydrology and geology, environmental impact assessment, flood control and weir structures for a hydropower plant on River Wuye at 885 kW. In addition, when River Wuye has low flow, wind and solar power plants could be deployed to provide the shortfall in electricity supply to the University